Stimulated emission of dark matter axion from condensed matter excitations - Naoto Yokoi; Eiji Saitoh (Journal of High Energy Physics, 2018)
Abstract We discuss a possible principle for detecting dark matter axions in galactic halos. If axions constitute a condensate in the Milky Way, stimulated emissions of the axions from a type of excitation in condensed matter can be detectable. We provide general mechanism for the dark matter emission, and, as a concrete example, an emission of dark matter axions from magnetic vortex strings in a type II superconductor is investigated along with possible experimental signatures.